Perceptions of General Education Teachers Working in Inclusive Schools in Armenia: A Preliminary Study - Harutyunyan, Marianna (Pedagogika, 2024)
In Armenia, the inclusion of students with special needs in regular classrooms underscores the need for robust support for teachers, students, and communities. This article explores general education teachers’ views on inclusion, emphasizing the need for extensive training and better resources to achieve effective inclusivity.